A call for collaboration on respectful, person-centered health care in family planning and maternal health. Issue 1 (December 2017) - Holt, Kelsey; Caglia, Jacquelyn; Peca, Emily; Sherry, James; Langer, Ana
Abstract Background Striking tales of people judged, disrespected, or abused in reproductive, maternal, newborn, child, and adolescent health (RMNCAH) services are commonly exchanged among friends and families throughout the world while remaining sorely under-addressed in global health. Disrespect and abuse of individuals and providers in health services across the RMNCAH continuum must be stopped through collaborative, multi-tiered efforts. Call for collaboration A new focus on health care quality in the Sustainable Development Goals offers an opportunity to seriously reexamine user experiences and their impact on health care utilization. The new framework provides an opening to redress the insidious problem of negative interactions with care across the RMNCAH services continuum and redraft the blueprint for service delivery and performance measurement, placing individuals and their needs at the center. Both the maternal health and family planning fields are at a turning point in their histories of defining and addressing individuals' experiences of care. In this commentary, we review these histories and the current state-of-the-art in both fields. Though the approaches and language in each sub-field vary, person-centered care principles related to the essential role of individuals' preferences, needs and values, and the importance of informed decision-making, respect, privacy and confidentiality, and non-discrimination, are integral to all. Promoting respectful, person-centered care also requires recognizing the factors that lead to poor treatment of clients, including gender norms and unsupportive working conditions for providers. Lessons can be learned from innovative efforts across the continuum to support health care providers to provide respectful, person-centered care. Conclusion Efforts in the maternal health and family planning fields to define respectful, person-centered care provide a useful foundation from which to connect across the continuum of RMNCAH services. Now is the time to creatively work together to develop new approaches for promoting respectful treatment of individuals in all RMNCAH services.